TRADISI ANDUNG DALAM UPACARA ADAT KEMATIAN SAUR MATUA MASYARAKAT BATAK TOBA DI KELURAHAN PALAS PEKANBARU - Sabeilai, Wilda Veronica; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Indonesia has a wealth of traditions that are spread in each region. Tradition as the nation's cultural wealth is one form of regional cultural expression that is very valuable, not only storing the cultural values of a traditional society but also can be the culture of a new society. Among the surviving traditions, one of them is in the Andung tradition which is in the custom of the death of the Batak Toba people. Andung is one of the traditions of the culture produced by the Batak Toba people. Andung is one of the traditions that is still used by the Batak people, especially the Batak Toba people. The purpose of this study is 1) Find out the Protestant Christianity's view of Death. 2) Find out the meaning of the Andung at the Batak Toba Saur Matua Death Ceremony in Palas Village 3) Find out the function of the Andung for the Batak Toba community in the Palas Village 4) Find out how to present the Andung in the Batak Toba Saur Matua Death Ceremony in the Palas Village. As for this study using descriptive qualitative methods and data obtained from interviews data and obtained from books and archives. The results of this study are to find out the tradition of andung that existed in the death of the Batak Toba community in the Palas Village. In addition to expressing things that revolved around feelings of disappointment and emotion by The renderer andung there were also expressions in the form of messages, prayers, and hopes for people who died..Key Words: Andung, Death, Batak